Cut loose TIMP-1: an emerging cytokine in inflammation. Issue 5 (May 2023) - Schoeps, Benjamin; Frädrich, Julian; Krüger, Achim
Abstract : Appreciation of the entire biological impact of an individual protein can be hampered by its original naming based on one function only. Tissue inhibitor of metalloproteinases-1 (TIMP-1), mostly known for its eponymous function to inhibit metalloproteinases, exhibits only a fraction of its cellular effects via this feature. Recently, TIMP-1 emerged as a potent cytokine acting via various cell-surface receptors, explaining a so-far under-appreciated role of TIMP-1-mediated signaling on immune cells. This, at least partly, resolved why elevated blood levels of TIMP-1 correlate with progression of numerous inflammatory diseases. Here, we emphasize the necessity of unbiased name-independent recognition of structure-function relationships to properly appreciate the biological potential of TIMP-1 and other cytokines in complex physiological processes such as inflammation. Highlights: The functional diversity of living cells is significantly determined by protein multifunctionality. This multifunctionality is based mostly on differential interaction of a given protein with different molecules, such as proteins or DNA, triggering very different downstream processes. Original naming of proteins is based mostly on one function only, and can obscure the appreciation of protein multifunctionality in the scientific community, for which tissue inhibitor of metalloproteinases-1 (TIMP-1) is a perfect example. From clinical evidence, TIMP-1 emerges as an important regulator of inflammatory processes. TIMP-1 is detected, at elevated levels, in the blood of patients with an exceptionally wide range of inflammation-associated diseases. Another interesting link of TIMP-1 with the immune system recently became evident when invariant chain (CD74) was discovered as a new signaling-inducing receptor of TIMP-1.